A Comparison of Hospital Area Measurement in Germany, Canada, Australia, and the United States: Part 1. (July 2022) - Viergutz, Hannah-Kathrin Silja; Apple, Michael
Objectives: This article compares national standards for area measurements of healthcare facilities in four countries and examines the risks and differences that can arise when comparing building areas of healthcare facilities internationally. Background: In the planning and management of healthcare facilities, the utilization and comparison of building floor areas plays a major role. Differences in terminology, classification, and methodology help to reduce planning and cost risks when applied on a local and national level. The proper allocation of building floor space is vital in the design of room programs, determination of floor space, construction costs, and operating costs. Methods: Each of the four hospital area measurement standards is compared to discern similarities and differences. Results: Most countries use a three-tier system of hospital area measurement: building gross area, department gross area, and department net area. Few differences were found between country standards for department area, though the German standards do not fully address this tier. Variation is found in whether a country includes certain functions in the hospital area—such as research space, shell space, or central energy plants—which can have a significant impact on the overall hospital area. Conclusions: This article informs further development of individual country standards and highlights principles to consider for international hospital area comparison.